Importance of development of STEM education for petrology and mineralogy - Takebayashi, Tomohiro; Kumano, Yoshisuke (Jurnal Inovasi Pendidikan IPA, 2018)
Rocks and minerals are very important materials for studying Earth Sciences. They are used to investigate the planetary history and evolution and are utilized as resources to support our lives. At present, it is critical for all countries to secure a stable supply of mineral resources, and it is necessary to understand the deposits and the growing mechanisms of minerals. In Japan, elementary and junior high school students study igneous and sedimentary rocks and some other kinds of minerals. In this research, we conducted a questionnaire for 154 Japanese junior high school students to investigate their 1) knowledge of minerals, and 2) petrology and mineralogy with respect to usefulness of rocks and minerals to our living. First, about 95% of the students could answer the names of the stone, including those who mainly answered jewel names. However, ~56% students could not answer the benefits of minerals.In high school, 36% students learned Basic Earth Sciences and 1.2% learned Earth Sciences (MEXT 2017). There is concern that most of the Japanese people have few opportunities to learn Earth Sciences. As NGSS showed in 2013, Earth and Space Science are major fields of STEM learning. Conclusively, it is necessary to stop memorizing subjects and instead modify the Earth Sciences with respect to STEM education. In this paper, we discuss the student's attitudes towards petrology and mineralogy so as to propose the Earth STEM education.